The effect of glass fiber reinforcement on the thermal properties of PETG - Zayden Chambers (The Young Researcher)
In the additive manufacturing industry, many polymer composites have properties - thermal and mechanical - that are unknown. The purpose of this study was to determine the key thermal properties of Polyethylene Terephthalate Glycol (PETG) with and without 15% glass fiber to understand the extent to which the glass fiber (GF) reinforcement affected the thermal properties of the thermoplastic. The PETG and PETG GF samples were produced via Fused Deposition Modeling (FDM). The samples were then weighed and tested using Differential Scanning Calorimetry (DSC), Thermogravimetric Analysis (TGA), and a Dynamic Mechanical Analysis (DMA). The change in thermal properties given by these instruments suggests that the glass fiber has a minimal effect on the key thermal properties when reinforcing PETG. These findings imply that using a material like PETG GF is not recommended for applications that require high temperatures.